2020
DOI: 10.1016/j.bpj.2020.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Factor 4 Interactions with Short Heparin Oligomers: Implications for Folding and Assembly

Abstract: Association of platelet factor 4 (PF4) with heparin is a first step in formation of aggregates implicated in the development of heparin-induced thrombocytopenia (HIT), a potentially fatal immune disorder affecting 1-5% of patients receiving heparin. Despite being a critically important element in HIT etiology, relatively little is known about the specific molecular mechanism of PF4-heparin interactions. This work uses native mass spectrometry to investigate PF4 interactions with relatively short heparin chains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 48 publications
(65 reference statements)
3
10
0
Order By: Relevance
“…While heparinoids as short as decasaccharides 38 ). Our previous work 22 demonstrated that such heparinoids (dp10) are incapable of PF4 bridging, 22 and the results of the present study indicate that even heparin fragments that are twice as long (dp20) are not sufficiently large for PF4 bridging.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…While heparinoids as short as decasaccharides 38 ). Our previous work 22 demonstrated that such heparinoids (dp10) are incapable of PF4 bridging, 22 and the results of the present study indicate that even heparin fragments that are twice as long (dp20) are not sufficiently large for PF4 bridging.…”
Section: Discussionsupporting
confidence: 58%
“…Previously we have shown that short heparin fragments (at least up to a decasaccharide level, dp10) are not sufficient for PF4 bridging (instead, multiple heparinoids associate with a single PF4 tetramer). 22 Similar behavior is exhibited by significantly longer chains, such as dp20 (the length that corresponds to an average size of the low-molecular weight heparin products, LMWH 23 ), as can be seen in Figure 1A. Incubation of dp20 with PF4 at an approximately equimolar ratio gives rise to an abundant ionic signal corresponding to a PF4•(dp20) 2 complex, although the 1:1 protein/heparinoid complexes are also observed (Figure 1A, top).…”
Section: Pf4/heparin Association: Polyanion Chain Length As the Major...mentioning
confidence: 99%
“…Addition of a structurally homogeneous pentasaccharide heparin mimetic (fondaparinux) to the RBD solution results in a noticeable shift of the ionic signal in native MS ( Figure 1 B). The magnitude of this shift (1521 Da) correlates with the ligand mass (1505 Da); importantly, only 1:1 protein/ligand complexes are observed (in contrast to high-pI proteins, which act as heparin “sponges” by accommodating multiple polyanionic chains 29 ). Similar behavior is observed when a fixed-length heparin oligomer (eicosasaccharide, or dp20) is added to the RBD solution ( Figure 1 C).…”
Section: Resultsmentioning
confidence: 99%
“…Decavanadate is a versatile member of the POM family displaying a variety of unique properties that can be exploited for a range of diverse applications. Our own interest in this molecule stems from its polyanionic nature that lends V10 as a viable candidate for applications in medicine as a disruptor of electrostatically-driven biopolymer interactions such as the platelet factor 4/heparin interactions 42 underlying the etiology of heparin-induced thrombocytopenia. The unique chemical properties of V10 are also enjoying considerable attention in areas ranging from chemical catalysis to electronics.…”
Section: Discussionmentioning
confidence: 99%